Ketika Keamanan Privasi Data Pribadi Semakin Rentan, Bagaimana Negara Seharusnya Berperan? - Zaid Zaid (Volksgeist: Jurnal Ilmu Hukum dan Konstitusi, 2021)
This article aims to determine the role and responsibility of the government in protecting personal data of all individuals, studied through normative research methods with a statutory and conceptual approach. The results of this study ultimately outlines what must be done by the government by forming law on personal data protection which guarantees its determination, implementation and supervision, forming its Sector Supervisory and Regulatory Agency, forming the Attorney General's Office to prepare a court that is responsive in handling personal data privacy violations.